IL-23 favours outgrowth of spondyloarthritis-associated pathobionts and suppresses host support for homeostatic microbiota. Issue 4 (11th April 2019) - Rehaume, Linda M; Matigian, Nicholas; Mehdi, Ahmed M; Lachner, Nancy; Bowerman, Kate L; Daly, Joshua; Lê Cao, Kim-Anh; Hugenholtz, Philip; Thomas, Ranjeny
Abstract : Objectives: Certain gut bacterial families, including Bacteroidaceae, Porphyromonadaceae and Prevotellaceae, are increased in people suffering from spondyloarthropathy (SpA), a disease group associated with IL23R signalling variants. To understand the relationship between host interleukin (IL)-23 signalling and gut bacterial dysbiosis in SpA, we inhibited IL-23 in dysbiotic ZAP-70-mutant SKG mice that develop IL-23-dependent SpA-like arthritis, psoriasis-like skin inflammation and Crohn's-like ileitis in response to microbial beta 1, 3-glucan (curdlan). Methods: We treated SKG mice weekly with anti-IL-23 or isotype mAb for 3 weeks, rested them for 3 weeks, then administered curdlan or saline. We collected faecal samples longitudinally, assessed arthritis, spondylitis, psoriasis and ileitis histologically, and analysed the microbiota community profiles using next-generation sequencing. We used multivariate sparse partial least squares discriminant analysis to identify operational taxonomic unit (OTU) signatures best classifying treatment groups and linear regression to develop a predictive model of disease severity. Results: IL-23p19 inhibition in naïve SKG mice decreased Bacteroidaceae, Porphyromonadaceae and Prevotellaceae. Abundance of Clostridiaceae and Lachnospiraceae families concomitantly increased, and curdlan-mediated SpA development decreased. Abundance of Enterobacteriaceae and Porphyromonadaceae family and reduction in Lachnospiraceae Dorea genus OTUs early in disease course were associated with disease severity in affected tissues. Conclusions: Dysbiosis in SKG mice reflects human SpA and is IL-23p19 dependent. In genetically susceptible hosts, IL-23p19 favours outgrowth of SpA-associated pathobionts and reduces support for homeostatic-inducing microbiota. The relative abundance of specific pathobionts is associated with disease severity.